Learning HTML and CSS LiveLessons - Kyrnin, Jennifer; Safari eBooks ([Place of publication not identified] : Addison-Wesley, 2016)
"In Learning HTML & CSS LiveLessons, Jennifer Kyrnin helps you master the core real-world skills you need to create your own web pages using HTML and CSS. Drawing on her experience helping thousands of people learn HTML, XML, and web design, Jennifer Kyrnin guides you from the absolute basics all the way to creating responsive web layouts and beyond. One step at a time, you learn how to create and post HTML to a hosting service; build a basic HTML document; write a CSS style sheet; use internal and external style sheets; build and style HTML text; create HTML5 outlines; adjust fonts and typography; choose and change colors; create CSS3 rounded corners; and even add HTML5 web video and audio. Everything's organized into bite-sized, self-contained lessons, so you can learn key HTML and CSS skills quickly and easily."--Resource description page.
Title from title screen (viewed December 7, 2015).
Presenter, Jennifer Kyrnin.
Keywords: HTML (Document markup language); Cascading style sheets; Web sites -- Design; Electronic books